2019
DOI: 10.1108/lht-12-2018-0198
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate students use of mobile apps to search library catalogs

Abstract: Purpose The purpose of this paper is to explore undergraduate students’ use of mobile apps to search library catalogs and analyze the problems students encountered. Student opinions and suggestions regarding mobile library apps were also examined. Design/methodology/approach A total of 16 undergraduates were observed and subjected to semi-structured interviews. Four tasks were assigned, and the participants used mobile apps and laptops to search library catalogs. Follow-up in-depth interviews were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Whether these medical students were already aware of the potential positive impacts of mobile learning remains unknown; recent studies have shown that HKU students are probably not very aware of the library services – especially the mobile services (Fong et al, 2020; Ko et al, 2015; Lam et al, 2019; Wai et al, 2018). In order to address this problem, the library should promote its mobile services (Chen, 2019), the benefits of mobile learning and the information literacy required (Aharony et al, 2020; Allard et al, 2020; Rantala et al, 2019), as well as design more innovative information services to attract patrons (Wójcik, 2019). Educators should also augment the curriculum to maximize exposing students to mobile learning and integrate learning activities in mobile platforms (Aharony, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Whether these medical students were already aware of the potential positive impacts of mobile learning remains unknown; recent studies have shown that HKU students are probably not very aware of the library services – especially the mobile services (Fong et al, 2020; Ko et al, 2015; Lam et al, 2019; Wai et al, 2018). In order to address this problem, the library should promote its mobile services (Chen, 2019), the benefits of mobile learning and the information literacy required (Aharony et al, 2020; Allard et al, 2020; Rantala et al, 2019), as well as design more innovative information services to attract patrons (Wójcik, 2019). Educators should also augment the curriculum to maximize exposing students to mobile learning and integrate learning activities in mobile platforms (Aharony, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental influences represent external environmental effects, such as cultural, social and family contexts, whereas individual differences refer to consumers’ internal characteristics. Further, the convenient and fast means of communication brought by the Internet have changed people’s lifestyles in information provision and acquisition, especially under the current ubiquitous mobile internet connectivity (Chen, 2019; Gong et al , 2017; Fan et al , 2020; Liang et al , 2017; Dorcic et al , 2019). In particular, wide internet availability with smartphones during travel has significantly changed tourists’ information search behavior (Ho et al , 2016; Kang et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The dynamics of online communications are changing as social media keeps evolving (Sigala et al , 2016) and augment platforms to maintain offline relationships. Moreover, accelerated development in mobile computing, particularly with the adoption of apps for traveling, has created new locales for information search and use (Wang et al , 2011; Gong et al , 2017; Chen, 2019; Fan et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Also, SNS enables people to read and discuss the news simultaneously, changing their news discussion duration and location. Readers can search for their preferences (Shim et al , 2015) anytime, anywhere (Chen, 2019), while SNS can also push timely news to readers with artificial intelligence algorithms according to usage history. The changes in news discussion duration and location could also be due to the convenience of discussing news online without time and location limitations.…”
Section: Discussionmentioning
confidence: 99%